Narodziny dzieci Michała Kazimierza Radziwiłła „Rybeńki” w świetle jego diariusza z lat 1722–1761 - Janicka, Jowita (Biuletyn Historii Wychowania, 2023)
Michał Kazimierz Radziwiłł, known as “Rybeńko” (1702–1762), was married twice. In 1725, he wed Franciszka Urszula née Wiśniowiecka (1705–1753), and following her death, he entered into a second marriage in 1754 with Anna Ludwika née Mycielska (1729–1771). Both unions produced numerous children, whose exact times of birth were meticulously recorded by their father in his diary, kept between 1722 and 1761. The arrival of a child was accompanied by a spectrum of emotions, ranging from joy to fear. Yet each such event was, in its own way, unique and meaningful–not only because it ensured the continuation of the family line, but also because a larger number of children enabled the family to fulfil all the roles assigned to it. This article focuses on the key moments in the marital life of Michał Kazimierz Radziwiłł “Rybeńko”, namely the births of his children. The selected source excerpts allow us to explore the emotional responses of the author to these events, as well as the practices and customs that accompanied them.